Language, autism and alternative augmentative communication - Reaño, Ernesto (2022)
Communication is a human right. Alternative augmentative communication systems are essential assistive technologies for full access for non-speaking autistic people. In this article we analyze the development of communication in autism and its main differences with neurotypical forms based on joint attention and shared intentionality. Transcending the logocentrism that dominates the "should be" of human communication, we can see in the alternative forms of communication and in the associated devices, systems of interaction as valid as orality. What is important is the functionality of the system in relation to the needs of each individual in the exercise of their right to communication.